2000
DOI: 10.4269/ajtmh.2000.62.132
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic tools for malaria surveillance in an urban setting of low endemicity along the Colombian Pacific coast.

Abstract: Abstract. An evaluation of 3 different methods for malaria diagnosis was carried out in an urban area of low endemicity on the Pacific coast of Colombia. Samples were collected from 833 symptomatic patients at a malaria clinic and examined by the polymerase chain reaction (PCR), quantitative buffy coat (QBC; Becton Dickinson, Franklin Lakes, NJ) method, and the traditional thick blood smear. The prevalence of Plasmodium falciparum malaria was 5.88% by thick blood smear, 7.34% by the QBC method, and 21.87% by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…While malaria microscopy may be capable of detecting very low parasite densities in some specialized centers (10-50 parasites/L), microscopy of blood films collected under conditions commonly present in many malaria-endemic areas (e.g., the present study) has been demonstrated to miss many cases with low-density parasitemias. [24][25][26][27][28] Other studies have demonstrated that RDTs can sometimes detect parasite densities that only the best microscopists might reliably identify. 29 Initial comparison of these samples by microscopy showed many apparent false-positive RDTs results, 11 similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…While malaria microscopy may be capable of detecting very low parasite densities in some specialized centers (10-50 parasites/L), microscopy of blood films collected under conditions commonly present in many malaria-endemic areas (e.g., the present study) has been demonstrated to miss many cases with low-density parasitemias. [24][25][26][27][28] Other studies have demonstrated that RDTs can sometimes detect parasite densities that only the best microscopists might reliably identify. 29 Initial comparison of these samples by microscopy showed many apparent false-positive RDTs results, 11 similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Entre 2000 y 2010, se reportaron al año entre 60 y 300 casos, con predominio de P. vivax (>70 %) y con un IPA inferior a 1,0, lo cual clasifica a este municipio como de bajo riesgo para la transmisión de la malaria (22). Sin embargo, aunque en este municipio no se registra un mayor número de casos de malaria, la transmisión se caracteriza por estar localizada en zonas periurbanas, evento que ha sido considerado como un problema de salud pública dado el riesgo de urbanización de la enfermedad (23,24). Esta transmisión periurbana ha sido favorecida por las condiciones ambientales y de desarrollo urbano, que han permitido la creación de ambientes propicios para la permanencia y proliferación de los vectores en Villavicencio, muy particularmente de An.…”
unclassified
“…15,[30][31][32] The occurrence of low-density transient parasitemia has been described as a common phenomenon in P. vivax sporozoite infection in nonhuman primates. 29,33,34 This low density, plus the typical spontaneous resolution of parasitemia, necessitates the use of a sensitive diagnostic method such as PCR 35,36 to study the immune dynamic responses to both the pre-erythrocytic and the blood stage phases of P. vivax infection.…”
Section: Discussionmentioning
confidence: 99%